Evaluasi Rancangan Geometri Peledakan Berdasarkan Hasil Fragmentasi Batuan dan Getaran Tanah Pada PT. Koto Alam Sejahtera Kabupaten Lima Puluh Kota Provinsi Sumatera Barat. - Muhammad Ilham Cahyadi; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2019)
Abstarct. Administratively, the mining location of  PT. Koto Alam Sejahtera is located in Jorong Polong Duo, Nagari Koto Alam, Pangkalan Koto Baru, Lima Puluh Kota District, West Sumatra Province.Explosive hole drilling activities at PT. Koto Alam Sejahtera uses the Furukawa Rock Drill PCR200 engine and the explosives used are Pindad ANFO (PANFO).Based on the distribution analysis of rock fragmentation results from actual blasting geometry data, the average rock fragmentation results from blasting (for 4 blasting times) that passed at 60 cm in size with desktop split software was 76,88%.Based on the calculation of ground vibration from the actual data of blasting geometry using the Du Pont / USBM predictor method, the PPV values exceeding 5 mm / s occurred on February 17 and 22 2018, with a PPV value of 6,31 mm / s and 5,76 mm / s.Based on the results of split desktop software analysis, the results of rock fragmentation in the proposed design blasting geometry is 86,22%.Based on the results of the calculation of ground vibration of the Du Pont / USBM predictor method, the value of PPV in the proposed design of II blasting geometry was 4,80 mm / s.Keywords: ANFO, Blasting Geometry, Ground Vibration, Kuz Ram, Rock Fragmentation, USBM Predictor.